Pancreatic carcinoids (serotonin-producing pancreatic neuroendocrine neoplasms): Report of 5 cases and review of the literature. Issue 16 (April 2017) - Tsoukalas, Nikolaos; Chatzellis, Eleftherios; Rontogianni, Dimitra; Alexandraki, Krystallenia I.; Boutzios, Georgios; Angelousi, Anna; Kaltsas, Gregory
Abstract: Introduction: Pancreatic neuroendocrine neoplasms (pNENs) are relatively rare tumors representing 1% to 2% of all pancreatic neoplasms. These tumors can secrete a variety of biologically active substances giving rise to distinct clinical symptoms or can be clinically nonfunctioning. Apart from insulinomas and gastrinomas, which constitute the majority of functioning pNENs, some tumors may secrete serotonin presenting with the features of the carcinoid syndrome. These so-called pancreatic carcinoids are considered relatively rare tumors and are associated with increased urinary levels of 5-hydroxyindoleacetic acid (5-HIAA). It has recently been suggested that the prevalence of such tumors might be underestimated. Cases: We present a series of 5 patients from our database of 138 pNENs (5/138, 3.62%), harboring serotonin-producing pNENs and describe their distinctive clinical, biochemical, histopathological features, and response to treatment along with a review of the relevant available literature. Conclusion: Such tumors are considered rare, although this may be an underestimate as systematic screening for the presence of serotonin in tissue or elevated urinary 5-HIAA levels in patients with apparently nonfunctioning pNENs is not currently recommended. In order to reach such a consensus, data from large prospective studies are needed in order to evaluate the impact of this type of tumors in survival and clinical outcome, since some studies have suggested a worse prognosis.